Traffic scheduling and link sharing mechanisms for controlled load service / Chin Yun Choong - Chin , Yun Choong (2000)
The project studies and develops a simulator based on the link-sharing and traffic scheduling mechanism for Controlled Load service. The simulation adopts some of the features of the Class Based Queueing. The main factors that determine whether a packet scheduling algorithm is able to support integrated services or differentiated services on Internet is the ability to provide bandwidth guarantee. It is important to provide guarantee for minimum bandwidth when there are enough demands to ensure competing data flows do· not degrade each others' performance. The objective of this project is to observe the performance of the link-sharing and traffic scheduling mechanism in providing bandwidth guarantee. Several experiments were carried out and can be divided into two main parts, the experiments with the "borrow" mechanism activated and the experiment without the borrow mechanism. These two parts were tested under different link usage and different bandwidth allocation to determine the efficiency of the ''borrow" mechanism. We expect the number of dropped packets will decrease especially during congestion time when the "borrow" mechanism is activated. We also expect the mechanism can provide bandwidth guarantee when there are enough resources. The results indicate that, the link-sharing and traffic scheduling mechanisms are capable of providing the bandwidth guarantee and of reducing the numbers of dropped packets during congestion period by using the "borrow" mechanism.